KONTEKSTUALISASI GAMELAN JAWA DI GEREJA BAPTIS INDONESIA (GBI) NGEMBAK - Alfa Kristanto (Sekolah Tinggi Theologia Abdiel, 2019)
This thesis aims to examine contextualization of Javanese gamelan in the liturgy of the worship at the Indonesian Baptist Church (GBI) Ngembak Tembalang. The approach used is interdisciplinary, using qualitative research methods, and interpretative case study research design. The research data was collected by observation technique, interview, and document study, and source triangulation technique to maintain its validity. Data analysis technique is done through the process of reduction, presentation, and conclusion (verification). The results of this study show that, the form of Javanese gamelan accompaniment music in liturgical worship at GBI Ngembak Tembalang is composed of two elements, namely the element of time and melody. Contextualization of Javanese gamelan in the liturgy of the worship at the Indonesian Baptist Church (GBI) Ngembak Tembalang consists of one model, namely model translation. On the model of translation is done through the efforts of Christian identity preservation, keeping mindful of the culture, history and social change, which is owned by the Baptist Church Indonesia (GBI) Ngembak Tembalang.